Thermal behavior of renewable diesel from sugar cane, biodiesel, fossil diesel and their blends - Conconi, Charles C.; Crnkovic, Paula Manoel [UNESP] (Elsevier, 2013)
Biofuels and their blends with fossil fuel are important energy resources, whose production and application have been largely increased internationally. This study focuses on the evaluation of the activation energy of the thermal decomposition of three pure fuels: farnesane (renewable diesel from sugar cane), biodiesel and fossil diesel and their blends (20% farnesene and 80% of fossil diesel - 20F80D and 20% farnesane, 50% fossil diesel and 30% biodiesel - 20F50D30B). Activation energy has been determined from thermogravimetry and Model-Free Kinetics. Results showed that not only the cetane number is important to understand the behavior of the fuels regarding ignition delay, but also the profile of the activation energy versus conversion curves shows that the chemical reactions are responsible for the performance at the beginning of the process. In addition, activation energy seemed to be suitable in describing reactivity in the case of blends of renewable and fossil fuels. © 2013 Elsevier B.V.
Keywords: Activation energy; Biofuels; Ignition delay; Thermogravimetry; Farnesene; Ignition delays; Model free kinetics; Renewable diesels; Thermal behaviors; Decomposition; Energy resources; Fossil fuels; Ignition; Sugar cane; Thermogravimetric analysis; Biodiesel